Bootstrapping Information from Corpora in a Cross-Linguistic Perspective - Alessandro Panunzi (Strumenti per la didattica e la ricerca, 2010)
The achievements of Romance language corpus-driven studies deserve more attention from the scientific community at the world level for both their quantity and quality. This book contains papers given at the 3rd International LABLITA Workshop in Corpus Linguistics (Italian Department, University of Florence, June 4th-5th 2008 ), and it aims at integrating new ideas and results derived from Romance language corpora in the framework of the overall achievements of Corpus Linguistics. The volume contains the contribution of a leading scholar of Corpus Linguistics (Douglas Biber), and a set of articles presented to Biber by notable European researchers and those from other countries. Papers report on long-term studies ranging from Italian to Spanish, French, Brazilian Portuguese and Japanese.